OP0120 Influence of epidemiology and ethnicity on systemic expression of primary sjÖgren syndrome in 9974 patients. (12th June 2018) - Retamozo, S; Acar-Denizli, N.; Fai Ng, W.; Zeher, M.; Rasmussen, A.; Seror, R.; Li, X.; Baldini, C.; Gottenberg, J.-E.; Danda, D.; Quartuccio, L.; Priori, R.; et al.
Abstract : Objectives: To analyse the influence of epidemiology and ethnicity on the clinical systemic presentation at diagnosis of primary Sjögren syndrome (SjS). Methods: The Big Data Sjögren Database included 10 475 worldwide patients from 22 countries fulfilling the 2002 criteria. Age at diagnosis, gender and ethnicity (77% White, 14% Asian, 6% Hispanic, 1% Black/African American, 2% others) were correlated with systemic involvement at diagnosis (retrospectively scored in 9974 patients using ESSDAI/clinESSDAI) Results: Men had higher mean ESSDAI (8.0 vs 5.9, p<0.001) and clinESSDAI (8.4 vs 6.1, p<0.001) in comparison with women; the domains more active in men included lymphadenopathy (p<0.001), glandular (p<0.001), pulmonary (p=0.001), PNS (p<0.001) and CNS (p<0.001). Highest scores were also reported in patients with young-onset disease (<35 years) with respect to older onset (>65 years) for ESSDAI (6.5 vs 5.6, p=0.002) and clinESSDAI (6.4 vs 5.8, p=0.034). Highest ESSDAI scores were reported in Black/African American, followed by White, Asian and Hispanic patients (6.7 vs 6.3 vs 5.4 vs 4.9, respectively, p<0.001). BAA patients showed the highest frequency of activity in lymphadenopathy, articular, PNS, CNS and biological domains, Whites in glandular, cutaneous and muscular, Asians in pulmonary, renal and haematological and Hispanics in the constitutional domain. Conclusions: This study provides the first evidence for a strong influence of epidemiology and ethnicity on the systemic phenotype at diagnosis of primary SjS Disclosure of Interest: None declared